Functionalization of reverse osmosis membrane with graphene oxide and polyacrylic acid to control biofouling and mineral scaling - Mohammad Y. Ashfaq (14152290) (2020)
The polyamide reverse osmosis (RO) membrane was modified with graphene oxide (GO), followed by polymerization of acrylic acid (used as an antiscalant) for the reduction of both biofouling and mineral scaling. After functionalization, the water contact angle reduced from 41.7 ± 4.5° for unmodified RO membrane to 24.4 ± 1.3° for the modified RO membranes, which showed that membrane hydrophilicity was significantly enhanced, in addition to the improvement in surface smoothness. The modified membranes were tested for their anti-scaling and anti-biofouling characteristics. When the mineral scaling test was performed using CaSO4 solution as feedwater, the permeate flux was reduced by only 3% as compared to the unmodified RO membrane which encountered up to 22% decline in flux by the end of the experiment. After the scaling test, the membrane surface was characterized by Scanning electron microscopy – energy-dispersive X-ray spectroscopy, Fourier transform infrared, and X-ray diffraction techniques. The results showed that the unmodified RO membrane was fully covered with gypsum precipitates. Whereas, the precipitates were detected only at the highly saturated zones of the water channel i.e. towards the exit of water flow. Additionally, the anti-bacterial test was performed through bacteriostasis rate determination, which showed that the modified membranes inhibited the growth of nearly 95% of the bacterial cells. Further experiments were also performed to investigate the inhibition of both scaling and biofouling by modified RO membranes. Thus, it was found that the polymer-modified GO coated RO membranes were able to diminish both gypsum scaling and biofilm formation demonstrating their potential to control different types of membrane fouling. Other Information Published in: Science of The Total Environment License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.scitotenv.2020.139500